Assessment of carbon footprint/emissions for solid waste added clay bricks productions / Aeshwini Singarajan - Aeshwini, Singarajan (2021)
Carbon footprint is an important component of ecological footprint because it quantifies the impact of specific products, activities, or industries in the form of carbon emissions. The higher the carbon footprint, the more greenhouse gases are emitted and contribute to climate change and global warming. The correlation between carbon footprint and waste recovery contributes towards combating environmental, social and economic issues through research and consistent applications. This comparative study was conducted based on three processes which are commercial, recovered clay bricks production and (S/S: stabilization and solidification) of SW204 sludge. The functional unit of 1kg is used throughout the study. The main aim of the study is to define the system boundary of the involved processes and access the carbon footprint. All the information used in this study for evaluation purpose is obtained from secondary data. The evaluation remarks that contributing factors to carbon dioxide emissions in the involved processes are electricity, water, fuel, raw material consumption, including solid waste and scheduled waste generation. The highest carbon footprint released is from process 3: (S/S) of SW204 sludge, which is 65 kg CO2 where it is rooted in high raw material consumption, solid waste generation and electricity usage: 63 kg CO2 ,1 kg CO2 ,0.73 kg CO2 (respective carbon emission). The disposal cost per kg of SW204 sludge is RM6.50, which is 70% higher than the other production costs discussed. Therefore, among several processes discussed, the best suggestion is the production of recovered clay bricks, which emit 21 kg CO2 with a production cost of RM1.15 per kg. The findings generated from this study will show the outline of circular economy benefits and how cost effective it is in the clay brick industry as well as carbon footprint contribution.